PECULIARITIES OF THE VALUE-SENSE SPHERE OF PEOPLE SURVIVED A TRAUMATIC EXPERIENCE - Motkov, Stanislav (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the theoretical research of the value-sense sphere in the personality structure of people survived traumatic experiences. The author analyzes the modern research works studied the value-sense sphere of people experienced traumatic events. The article shows that this topic is urgent nowadays; though the common approach to the peculiarities of value-sense sphere of people survived traumatic experiences doesn’t give proper and deep comprehension of this issue. To research theoretically some peculiarities and characteristics of separate components of value-sense sphere of people survived traumatic experiences is the task set in the article. The article proves that key changes of values and value orientations are reflected in loss of an individual’s own selfhood in a new non-typical situation. A traumatized individual experiences an inner conflict arisen because of the necessity to set new values or to choose drastically new approaches in achieving them. People who lost their value orientations begin to pattern their behaviour according to the basic, egoistic necessities. The article ascertains that an individual faces the problem of personal senses as a result of his/her traumatic experience. Senses, that were behavioural patterns for the individual before, can become irrelevant in a new situation. It evokes the feeling of inner feebleness, inability to be oriented in own existence and entity. Life sense orientations of such individual also undergo important changes. As a result of a traumatic experience, the individual loses faith and belief in benevolence of this world and, in its turn, becomes excessively suspicious, has feeling of mortification and resentment against other people, abnormal anxiety and uneasiness because of surrounding world dangers. Personal self-regard is changed to a great extent. Being unable to control a situation, such individual feels helplessness and feebleness, inability to influence his/her destiny and life. The individual has negative self-regard and feels negative regard and disrespect of other people. On the one hand, the individual craves for necessity of personal changes; on the other hand, this individual suffers and experiences fear of these changes. Very often self-condemnation appears because of own inability to influence properly a situation. However, as a consequence of such crisis of the value-sense sphere, the individual can achieve new accomplishments; this makes him/her more stress-resistant, mature, encourages to appreciate wider existential senses and values. The author summarizes the obtained data and establishes prospects for further research work.